2012
DOI: 10.1016/j.rse.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Using the NOAA Advanced Very High Resolution Radiometer to characterise temporal and spatial trends in water temperature of large European lakes

Abstract: (This is a sample cover image for this issue. The actual cover is not yet available at this time.)This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Lakes are majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Various studies (e.g. Oesch et al, 2005;Politi et al, 2012) have shown that LSWT over Europe can be derived with reasonable accuracy making use of global split-window approaches designed for SST retrievals by comparing in situ observations of ocean water temperature with satellite data. These methods, however, are intended to match the global atmospheric conditions over ocean surfaces which may substantially differ from the continental conditions found over some inland water bodies.…”
Section: Split-window Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies (e.g. Oesch et al, 2005;Politi et al, 2012) have shown that LSWT over Europe can be derived with reasonable accuracy making use of global split-window approaches designed for SST retrievals by comparing in situ observations of ocean water temperature with satellite data. These methods, however, are intended to match the global atmospheric conditions over ocean surfaces which may substantially differ from the continental conditions found over some inland water bodies.…”
Section: Split-window Approachmentioning
confidence: 99%
“…Hulley et al, 2011;MacCallum and Merchant, 2012) have elaborated more accurate methods to retrieve LSWT by utilising radiative transfer codes and atmospheric data from numerical weather prediction (NWP) reanalyses and/or analyses data to better reproduce the atmospheric conditions in such regions and also account for the lake specific altitude. In addition, the latter methods have the advantage of being completely independent of in situ data and therefore are also applicable to situations far away from in situ observations, whereas Politi et al (2012), for instance, use in situ observations to adapt their retrievals for local effects.…”
Section: Split-window Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The red triangles represent the estimated influence of SWCs for different validated LSWT products in literature. (i [11]; ii [29]; iii [37]; iv [12]; v [38]; vi [13]; vii [18]; viii [20]). …”
Section: Discussionmentioning
confidence: 99%
“…Burrage et al, 2008;Klemas, 2011), while sea surface temperature can be retrieved from the measurements in the thermal infrared between 8 and 14 µm (e.g. MacCallum and Merchant, 2012;Politi et al, 2012;Merchant et al, 2013). This review is restricted to measurements that can be made by optical remote sensing from satellite platforms and will primarily consider Chl-a, PC, TSM and CDOM.…”
Section: Introductionmentioning
confidence: 99%